The Relationship of Indoor and Outdoor Thermal Variables to Create an Energy-Efficient Modern House in the Tropical Mountains of Indonesia - Hermawan Hermawan; Jozef Švajlenka; Elina Mohd Husini (IntechOpen, 2026)
Non-Indexed Publication